The essential guide to religious traditions and spirituality for health care providers - Jeffers, Steven L. author.
1 online resource (1048 pages)
Keywords: This extraordinary compendium of religious traditions is invaluable to all healthcare providers. The user-friendly resource contains specific and detailed information on faith traditions vital for providing optimal spiritual care in a clinical setting. A series of inspirational introductory chapters promote the importance of spiritual well-being as a vital component in whole person care, but the majority of the book forms a compilation of articles from a wide-ranging expert panel of contributors. Ideal for quick reference, the A-Z organisation from American Indian Spirituality to Zoroastrianism is presented in a clear and logical format, covering: History and Facts Basic Teachings Basic Practices Principles for Clinical Care. Dietary Issues. General Medical Beliefs. Specific Medical Issues. Gender and Personal Issues Principles for Spiritual Care Through the Cycles of Life Concepts of Living and Dying for Spiritual Support. During Birth. During Illness. During End of Life Care of the Body Organ and Tissue Donation Scriptures, Inspirational Readings and Prayers.